2019
DOI: 10.1128/aac.00240-19
|View full text |Cite
|
Sign up to set email alerts
|

First-Time-in-Human Study and Prediction of Early Bactericidal Activity for GSK3036656, a Potent Leucyl-tRNA Synthetase Inhibitor for Tuberculosis Treatment

Abstract: This first-time-in-human (FTIH) study evaluated the safety, tolerability, pharmacokinetics, and food effect of single and repeat oral doses of GSK3036656, a leucyl-tRNA synthetase inhibitor. In part A, GSK3036656 single doses of 5 mg (fed and fasted), 15 mg, and 25 mg and placebo were administered. In part B, repeat doses of 5 and 15 mg and placebo were administered for 14 days once daily. GSK3036656 showed dose-proportional increase following single-dose administration and after dosing for 14 days. The maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 22 publications
(25 reference statements)
1
48
0
Order By: Relevance
“…New chemical scaffold with novel inhibition mechanism against Mtb is being actively sought. An oxaborole compound GSK3036656 that inhibits Mtb leucyl-tRNA synthetase is currently undergoing clinical trial (6).…”
Section: Introductionmentioning
confidence: 99%
“…New chemical scaffold with novel inhibition mechanism against Mtb is being actively sought. An oxaborole compound GSK3036656 that inhibits Mtb leucyl-tRNA synthetase is currently undergoing clinical trial (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, its development was halted in phase II clinical trials due to the rapid emergence of resistance [ 171 ]. Furthermore, a series of novel 3-aminomethyl-4-halogeno-benzoxaboroles were synthesized and preclinically evaluated by GSK as selective inhibitors against Mycobacterium tuberculosis LeuRS (Mtb-LeuRS) [ 172 ]. The promising lead compound GSK3036656 ( Figure 12 a) demonstrated a MIC value of 23.5 ng/mL against M. tuberculosis strain H37Rv and an IC 50 value of 58.8 ng/mL against Mtb-LeuRS in vitro.…”
Section: Natural and Synthetic Aarss Inhibitors And Their Inhibitomentioning
confidence: 99%
“…The promising lead compound GSK3036656 ( Figure 12 a) demonstrated a MIC value of 23.5 ng/mL against M. tuberculosis strain H37Rv and an IC 50 value of 58.8 ng/mL against Mtb-LeuRS in vitro. In addition, this compound showed no serious side effects following single or multiple doses and was selected for further clinical studies [ 172 ]. Most recently a series of benzhydrol-oxaborole derivatives were identified that selectively inhibited S. pneumoniae LeuRS and demonstrated anti-pneumococcal activity, with the best compound having a MIC of 4 μg/mL [ 173 ].…”
Section: Natural and Synthetic Aarss Inhibitors And Their Inhibitomentioning
confidence: 99%
“…Early examples of Gates MRI's investment in the model‐informed drug development (MIDD) approach include physiologically‐based pharmacokinetic modeling to inform first‐in‐human dose selection for a phase I trial, population‐pharmacokinetic modeling to inform sampling schemes for a phase II early bactericidal activity trial, and extensive clinical trial simulation to support sample size requirements, subject selection criteria, and evaluate the interferon‐gamma release assay threshold sensitivity on end point determination for our upcoming BCG revaccination trial. There is a clear roadmap for the model‐informed drug development approach laid out by our industrial and academic partners in collaboration with colleagues at the Gates Foundation. Our commitment is to adopt this roadmap with the guidance of global regulatory authorities.…”
Section: Possible Alternatives To the Status Quo: Tb Drugsmentioning
confidence: 99%